ANALYSING THE INVISIBLE BARRIERS: STUDENT UNDERSTANDING AND CONTEXTUAL OBSTACLES IN GEOGRAPHY ONLINE LEARNING - Andri Estining Sejati; Nasarudin Nasarudin; Putri Tipa Anasi; La Ode Muhammad Ruspan Takasi; Mimin Mintarsih; Jaynudin Jaynudin; Resti Karmila; La Ode Nursalam (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
Online learning poses significant challenges to conceptual understanding in geography, particularly in rural Indonesian settings characterized by infrastructure and social limitations. This study aims to analyze the level of student understanding and identify fundamental obstacles in online geography learning at Senior High School State 2 Mawasangka Tengah. A quantitative approach was employed involving 25 Class X Social Science students and one geography teacher. Data were collected via essay tests (10 items on soil formation and distribution) and unstructured interviews. Data analysis utilized descriptive quantitative methods with percentages. Student understanding levels were categorized as high (32%; 8 students), medium (44%; 11 students), and low (24%; 6 students), with the medium category being dominant. Major obstacles included low internal learning motivation (laziness), language barriers in understanding instructional Indonesian, group learning adaptation issues, limited learning time allocation (90 minutes), social environment influences, and digital infrastructure limitations. There is a critical need for adaptive online geography instruction that addresses student disengagement, language barriers, time constraints, and socio-environmental factors to enhance conceptual understanding in future online learning implementations.